"Nossos corpos também mudam": sexo, gênero e a invenção das categorias "travesti" e "transexual" no discurso científico - Leite Junior, Jorge (2008)
The goal of this work is to ponder the construction of the transvestite and transsexual categories in scientific discourse. Starting from the distinction between antiquity's hermaphrodite, more closely associated with magical and mythical notions, and modern medicine's pseudohermaphrodite, it can be seen how the latter became internalized through the discourse of psychological sciences. Throughout the 20th century, the transvestite and transsexual categories slowly developed from this conceptual basis, understanding the transit between sexes and genders as psychopathological manifestations